Exploiting the thermal potential of deep seawater for compensating losses in offshore hydraulic wind power transmission pipelines. Issue 10 (8th July 2016) - Sant, Tonio; Buhagiar, Daniel; Farrugia, Robert N.
Abstract : The use of hydraulic power transmission to transport offshore wind energy from deep offshore sites to shore may present a more feasible option for integrating wind farms with land‐based hydro‐energy storage systems. Yet the incurred losses resulting from fluid friction are significantly larger than those encountered in electrical power cables. This study investigates the possibility of compensating for such losses by exploiting cold deep‐seawater (DSW) from below thermoclines. A numerical study simulating a single large‐scale offshore wind turbine‐driven pump supplying DSW to shore across a pipeline in the Central Mediterranean is presented. Seawater leaving the grid‐connected hydroelectric power plant is allowed to flow through a centralised district air‐conditioning unit operating on a vapour compression cycle. Any shortfall in DSW supply due to lack of wind is compensated for by sea surface water to maintain a constant flow rate. The analysis is repeated for seawater pipelines having different sizes. It is shown that the deep seawater supply from the offshore wind turbine, though being intermittent, reduces the energy consumption of the air‐conditioning system considerably. The resulting savings are found to compensate for a significant proportion of the losses encountered in the hydraulic transmission pipeline.